1995
DOI: 10.1139/b95-210
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of Vallisneria americana seeds and seedling light requirements in the Upper Mississippi River

Abstract: Vallisneria americana declined in backwaters of the Upper Mississippi River, U.S.A., after a drought in 1988. To determine whether viable seeds of V. americana occurred in the seed bank of navigation pool 7, Lake Onalaska, the upper 5 cm of sediment was collected from 103 sites in May 1990. These sediment samples were kept in pots at a depth of 0.4, 0.8, and 1.2 m in an outdoor pond for 12 weeks. Vallisneria americana seeds germinated from sites throughout the lake, and some seedlings produced overwintering bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…and L. dubia ranked within the top five most dominant taxa for each of the seedbanks (Table IV). Other published accounts of UMR seed banks have been limited to aquatic species (Kimber et al, 1995;McFarland and Rogers, 1998) for UMR Navigation Pool 7 (Lake Onalaska). The arrays of submersed aquatic plant species that germinated in these studies are comparable to that found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…and L. dubia ranked within the top five most dominant taxa for each of the seedbanks (Table IV). Other published accounts of UMR seed banks have been limited to aquatic species (Kimber et al, 1995;McFarland and Rogers, 1998) for UMR Navigation Pool 7 (Lake Onalaska). The arrays of submersed aquatic plant species that germinated in these studies are comparable to that found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of suitable germination cues also could help explain why some species did not appear in the greenhouse assays (Stroh et al 2012). McFarland and Rogers (1998) had good success germinating seeds in a low-alkalinity culture solution (but see Kimber et al 1995). However, in most studies we encountered, investigators using the emergence method did not apply a chemical treatment to stimulate germination (e.g., Haag 1983, Bonis and Lepart 1994, ter Heerdt et al 1996, Stroh et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…McFarland and Rogers (1998) had good success germinating seeds in a low-alkalinity culture solution (but see Kimber et al 1995). However, in most studies we encountered, investigators using the emergence method did not apply a chemical treatment to stimulate germination (e.g., Haag 1983, Bonis and Lepart 1994, ter Heerdt et al 1996, Stroh et al 2012.…”
Section: Discussionmentioning
confidence: 99%